Penguatan Pemahaman Guru tentang STEM-Project Based Learning melalui Pelatihan Berbasis Praktik Baik - Gusti Firda Khairunnisa; Nur Qomaria; Subanji Subanji; Swasono Rahardjo; Slamet Slamet; Jamaliatul Badriyah (Abdimas Mandalika, 2026)
Abstract:  This community service program aimed to strengthen teachers’ understanding of STEM–Project Based Learning through a best-practice-based training approach. The program was conducted using a descriptive method in the form of a workshop involving 12 teachers at SMA Surya Buana Malang. The training included fundamental concepts, exploration of project-based learning characteristics, and sharing of best practices by experienced practitioners. Data were collected through pre- and post-training questionnaires as well as reflection surveys and analyzed descriptively using mean scores and percentages. The results indicated an improvement in teachers’ understanding, particularly in implementation aspects such as learning stages and project-based assessment. The most significant improvement was found in teachers’ readiness to implement the approach, with 83.33% of participants expressing readiness to apply STEM–Project Based Learning in their classrooms. In addition, participants perceived the training as relevant and meaningful. These findings suggest that best-practice-based training is effective in enhancing teachers’ understanding while fostering initial readiness to implement integrated learning approaches.Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat pemahaman guru tentang STEM–Project Based Learning melalui pelatihan berbasis praktik baik. Kegiatan dilaksanakan menggunakan pendekatan deskriptif dalam bentuk workshop yang melibatkan 12 guru di SMA Surya Buana Malang. Pelatihan mencakup penyampaian konsep dasar, eksplorasi karakteristik pembelajaran berbasis proyek, serta berbagi praktik baik oleh praktisi. Data dikumpulkan melalui angket sebelum dan sesudah pelatihan serta angket refleksi, kemudian dianalisis secara deskriptif menggunakan skor rata-rata dan persentase. Hasil menunjukkan adanya peningkatan pemahaman guru, terutama pada aspek implementatif seperti tahapan pembelajaran dan penilaian berbasis proyek. Peningkatan tertinggi terjadi pada aspek kesiapan guru untuk mengimplementasikan pembelajaran, dengan 83,33% peserta menyatakan siap mencoba STEM–Project Based Learning di kelas. Selain itu, peserta menilai pelatihan relevan dan memberikan pengalaman belajar yang bermakna. Temuan ini menunjukkan bahwa pelatihan berbasis praktik baik efektif dalam memperkuat pemahaman sekaligus mendorong kesiapan awal guru dalam mengimplementasikan pembelajaran yang terintegrasi.